Role of AMP-activated protein kinase in the molecular adaptation to endurance exercise - Winder, W. W.; Taylor, E. B.; Thomson, D. M. (Medicine & Science in Sports & Exercise, 2006)
What are the molecular signals induced by muscle contraction that result in an increase in GLUT4, hexokinase 2, mitochondrial oxidative enzymes, and other adaptations to endurance exercise training? Could repetitive activation of AMP-activated protein kinase (AMPK) be responsible in part? There is substantial evidence for a role of AMPK in inducing adaptations to endurance training: 1) AMPK is activated in response to muscle contraction; 2) chronic chemical activation of AMPK results in increases in GLUT4, hexokinase 2, UCP-3, and citric acid cycle enzymes; 3) muscle contraction and chemical activation of AMPK both result in increases in PGC-1[alpha], a transcriptional coactivator involved in stimulation of mitochondrial biogenesis; and 4) increases in muscle PGC-1[alpha], delta-aminolevulinic acid synthetase, and mitochondrial DNA induced by chronic creatine phosphate depletion in wild-type mice are not observed in dominant-negative AMPK mice. These observations lend credence to the hypothesis that AMPK activation induced by muscle contraction is responsible in part for adaptations to endurance exercise training.